EFEKTIVITAS MEDIA BERBASIS INFORMATION COMMUNICATION AND TECHNOLOGY DALAM MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMKN 1 BONE - Karnisah, Karnisah; Nursyirwan, Nursyirwan (JURNAL AL-QAYYIMAH, 2021)
This thesis discusses the Effectiveness of Media-Based Information Communication and Technology in Improving Student Learning Motivation and Achievement in Islamic Education Learning in Public Vocational Secondary Schools 1 Bone. Aiming to find out learning by using ICT media in order to improve motivation and learning achievement of class X students of Public Vocational Secondary Schools 1 Bone, learning achievement of Islamic religious education of class X students of Public Vocational Secondary Schools 1 Bone, and Effectiveness of ICT Media on student motivation and learning achievement at Public Vocational Secondary Schools 1 Bone.To obtain answers to the three main problems, the authors used the method of field research, this study included a type of qualitative research using three approaches namely; pedagogical, psychological, and sociological approaches. Data obtained through secondary data, namely questionnaires and interviews directly to respondents using four data collection techniques, cluster techniques, stratified, proportional and random techniques.Research results saw the most effective use of ICT is important. The computer and network media used in ICT learning are: Al-Qur'an program in word, Al-Qur'an Flash, Laptop, cellphone, E-Learning and video learning. And than The effectiveness of ICT Media on students' motivation and learning achievement, significantly increases the textbooks, given by the teacher they can have and given to students via WhatsApp. Therefore, increasing motivation and learning achievement through ICT media in Public Vocational Secondary Schools Bone is more effective compared to traditional and conventional learning.